2013
DOI: 10.1371/journal.pone.0063157
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbial Diversity in Pre-Weaned Dairy Calves as Described by Pyrosequencing of Metagenomic 16S rDNA. Associations of Faecalibacterium Species with Health and Growth

Abstract: In this study, we use barcoded pyrosequencing of the 16S rRNA gene to characterize the fecal microbiota of neonatal calves and identify possible relationships of certain microbiota profiles with health and weight gain. Fecal samples were obtained weekly from 61 calves from birth until weaning (seventh week of the calves' life). Firmicutes was the most prevalent phylum, with a prevalence ranging from 63.84% to 81.90%, followed by Bacteroidetes (8.36% to 23.93%), Proteobacteria (3.72% to 9.75%), Fusobacteria (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
273
7
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(330 citation statements)
references
References 32 publications
44
273
7
6
Order By: Relevance
“…The present study revealed a significantly higher prevalence of Faecalibacterium in large-intestinal communities than in communites in other GIT regions. A high abundance of F. prausnitzii in the feces was associated with increased weight gain and a decreased incidence of diarrhea in dairy calves (4). The fermentation of F. prausnitzii produces butyrate, which is the major energy source for colonic epithelial cells, and it also stimulates anti-inflammatory responses (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study revealed a significantly higher prevalence of Faecalibacterium in large-intestinal communities than in communites in other GIT regions. A high abundance of F. prausnitzii in the feces was associated with increased weight gain and a decreased incidence of diarrhea in dairy calves (4). The fermentation of F. prausnitzii produces butyrate, which is the major energy source for colonic epithelial cells, and it also stimulates anti-inflammatory responses (4).…”
Section: Discussionmentioning
confidence: 99%
“…A high abundance of F. prausnitzii in the feces was associated with increased weight gain and a decreased incidence of diarrhea in dairy calves (4). The fermentation of F. prausnitzii produces butyrate, which is the major energy source for colonic epithelial cells, and it also stimulates anti-inflammatory responses (4). Therefore, the observed higher prevalence of Faecalibacterium species in the large intestine of preweaned calves may be important for maintaining proper body weight and reducing enteric infections during early life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Clostridium butyricum has been shown effective as a poultry probiotic [48]. In addition, other butyrate producing bacteria such as Faecalibacterium prausnitzi, Roseburia faecis, and others may be associated with an healthy intestinal tract due the beneficial properties of this short chain fatty acid [49,50]. Some prebiotics also can improve the levels of F. prausnitzi in the intestine [51] and enrich the poultry litter.…”
Section: Effect Of Time and Treatments On Abundance Of Pioneer Colonimentioning
confidence: 99%
“…Increasing the production of ruminal butyrate could therefore benefit rumen development. Oikonomou et al (2013) found that a higher diversity and prevalence of the butyrate-producing bacteria, Faecalibacterium prausnitzii, in the rumen of 1-week old calves increased DWG postweaning compared to calves with a lower population of Faecalibacterium prausnitzii in the rumen. An intra-ruminal infusion of butyrate in cattle can also increase rumen papillae size and density (Shen et al 2005).…”
Section: Rumen Volatile Fatty Acidsmentioning
confidence: 85%